The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009 Conference on Lasers &Amp; Electro Optics &Amp; The Pacific Rim Conference on Lasers and Electro-Optics 2009
DOI: 10.1109/cleopr.2009.5292746
|View full text |Cite
|
Sign up to set email alerts
|

Laser crack-free cutting technique for thick and dense ceramics

Abstract: A new laser crack-free cutting technique for dense ceramics with thickness of 10 mm based on beam continuous piercing full through the workpieces is presented. The techology can be concluded as a feasible tool for cutting of thick and dense ceramics in complex path, even for 3D cutting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…When the energy density of a condense laser light is over a certain threshold irradiated on a work piece, it ablates, and as a result, it is cut. Different methods of laser cutting are presented in [7,8,9,10], for various materials and applications. Process threshold and cut depth varies depending on the material.…”
Section: Wafer Laser Groovingmentioning
confidence: 99%
“…When the energy density of a condense laser light is over a certain threshold irradiated on a work piece, it ablates, and as a result, it is cut. Different methods of laser cutting are presented in [7,8,9,10], for various materials and applications. Process threshold and cut depth varies depending on the material.…”
Section: Wafer Laser Groovingmentioning
confidence: 99%
“…With CO 2 lasers holes are usually cut rather than drilled which leads to larger diameters as compared to percussion or single pulse drilling. Yan et al (2012) have shown that using a digitally modulated 3.5 kW CO 2 laser it is possible to cut holes in 4.4 mm thick alumina, while Ji et al (2009) employed a 3.5 kW CO 2 laser and cut holes in 10 mm alumina. However, due to the long wavelength (large beam parameter product) both studies reveal problems in cutting bore diameters smaller than 100 m. In addition, Yan et al (2012) showed adverse impacts of a larger heat affected zone (HAZ) with associated changing of the aluminium-oxygen atomic ratio.…”
Section: Introductionmentioning
confidence: 98%